Prison, Mental Health, and Family Spillovers - Manudeep Bhuller; Laura Khoury; Katrine Vellesen Loken (Institute of Labor Economics (IZA), 2023)
Does prison cause mental health problems among inmates and their family members? Correlational studies tend to find much higher prevalence of mental health problems among inmates than in the general population, but remain silent on the issue of causality. We combine detailed Norwegian data on visits to health-care professionals with quasi-experimental designs to measure the impacts of incarceration on mental health-related visits by defendants and their family members. Our causal evidence consistently shows that the positive correlation is misleading: incarceration in fact lowers the prevalence of mental health-related visits among defendants. Family members, especially spouses, also experience positive mental health spillovers, while there are fewer episodes of child protection services involvement. We demonstrate that these effects last long after release and are unlikely driven by shifts in health-care demand holding health status constant. We interpret these findings in light of the rehabilitative role of correctional services in the Norwegian context.
Keywords: K42; I10; I18; 330; mental health; incarceration; family spillovers